PROBLEMS RELATED TO SPORTS AND NUTRITION OF STUDENTS FROM MEDICAL COLLEGE – PLOVDIV DURING ONLINE TRAINING - Y. Topuzova; M. Bonev (Trakia Journal of Sciences)
Goal: Modern technologies and digitalization require that higher education adopt online teaching methods. Current conditions, exacerbated by the ongoing COVID-19 pandemic, required most colleges and universities to transition to online teaching, which has its pros and cons. The effects of online learning on sports and nutrition are the subject of this paper – it is the writer’s goal to review and discuss the above topics as they relate to students from Medical College – Plovdiv. Methods: The study is conducted via a survey of Medical College students at random. Students represent a sample of both sexes, as well as a variety of majors, different levels of completed course work and different age groups. After completing the survey, statistical methods are used to extrapolate the data and sum up the main problems related to online education. Results: Online learning leads to a number of issues. The obtained results show the main negative factors observed to be: inactivity, lack of motivation and lack of acceptable conditions for physical education. Surveyed students also display higher propensity toward eating more often, eating larger quantities of food, as well as eating less healthy. All of the above could lead to increased body weight. Conclusions: Online education may be an acceptable alternative to many other topics, but as it relates to sports and nutrition it is very challenging to successfully replace the in-person method with online learning. This may lead to deteriorating health in students and the early onset of disease. Students may experience high blood pressure, diabetes, cardio-vascular disease and others. Therefore, it is very import to research the above topic and proper action to be taken to address and remedy the above-mentioned issues.